Hungarian Monitoring, 22 October 1989 . [Magyar rádiófigyelő], 1989. október 22 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Peaceful movements continue in the GDR - On the eve of the declaration of the Republic of Hungary - Foreign opinions on tomorrow's events Domestic Affairs: - Hungarian Democratic Forum (MDF) national meeting - October 23 commemorations begin - Entrepreneurs' Party formed - Zoltán Fábri days in Kassa/Kosice - Interview with GDR bishop W. Leich Külpolitika: - Az NDK-ban folytatódnak a békés megmozdulások - A Magyar Köztársaság kikiáltásának előestéjén. - Külföldi vélemények a holnapi esemény kapcsán Belpolitika: - MDF országos értekezlet - Elkezdődtek az október 23 - I megemlékezések - Megalakult a Vállalkozók Pártja - Fábri Zoltán napok Kassán - Interjú W. Leich NDK püspökkel